PERAN FAKTOR HARGA DIRI DAN PUSAT PENGENDALIAN DIRI TERHADAP PERILAKU SEKSUAL LELAKI SEKS DENGAN LELAKI DI JAKARTA TIMUR - Nugroho, Adi (Pusat BTDK, 2012)
AbstractBackground: Sexual Behavior among Men who have sex with Men (MSM) gives a large contribution in the chain of transmission of HIV. This study aims to analyze the role of personal factors in MSM in East Jakarta on sexual behavior in particular aspects of self-esteem and locus of control. Method: Research design used quantitative methods with cross sectional approach. Collecting data using purposive sampling technique of 224 respondents in East Jakarta with criteria: had sex with men in the last six months; not a transvestite; able to read and write, and are willing to become respondents. Sexual behavior, self-esteem and locus of controls were measured using self-completion questionnaire by the respondent accompanied by a research assistant. Data analysis was conducted to determine the different proportions of risky sexual behavior based on self-esteem and locus of control. Results: Most respondents have a high-risk sexual behavior (78.1%). About 45.1% of respondents had low self-esteem and 60.7% respondents had locus of control from within themselves. MSM with the locus of control from within has a relatively similar high risk sexual behavior as MSM who had locus of control from outside themselves (p=1.000). MSM with low self-esteem tend to have larger risk for high-risk sexual behavior than MSM who have high self-esteem (OR 1.95% CI 1.00-3.80). Conclusion: Low self-esteem on the MSM tends to increase the risk of their sexual behavior, so that it is recommended to develop methods of counseling and mentoring that contains material to increase self-esteem.